Epidemiologic Data of Vitamin D Deficiency and Its Implication in Cardio-Cerebrovascular Risk in a Southern Italian Population. (8th June 2021) - Capuano, Rocco; Marchese, Federica; Sica, Raffaella; Capuano, Eduardo; Manilia, Marzia; Iannone, Anna Grazia; D'Ambrosio, Alessandro; Bisecco, Alvino; Tedeschi, Gioacchino; Gallo, Antonio; Capuano, Vincenzo
Abstract : Background . Vitamin D (25(OH)D) deficiency is a prevalent condition worldwide. However, the highest prevalence rates of 25(OH)D deficiency have been attributed to regions with higher latitude. A close association between 25(OH)D and cardio-cerebrovascular (CCV) risk factors and major health problems has been identified. Aim . To establish the prevalence of 25(OH)D deficiency and to investigate the relationship between 25(OH)D levels and CCV risk factors (blood cholesterol, triglycerides, glucose concentrations, body mass index, and systolic and diastolic blood pressure) in a cohort representative of Southern Italy. Methods . The prevalence of 25(OH)D levels was evaluated in 1200 subjects aged 25–74 years (600 males and 600 females), enrolled in the "VIP" (from Italian for Irno Valley Prevention ) Project, whereas multiple linear regression analysis was used to determine the relationship between 25(OH)D levels and CCV risk factors. Results . Only 13.3% of females and 11.1% of males showed adequate serum concentrations of 25(OH)D (≥30 ng/ml), while 59.3% of females and 55.1% of males showed 25(OH)D deficient levels (<20 ng/ml). We observed an independent association between 25(OH)D concentrations and metabolic syndrome score, LDL cholesterol, HDL cholesterol, and corrected QT (cQT). Conclusions . We report a high prevalence of 25(OH)D deficiency across the largest Italian adult population studied so far and, in particular, the first across Southern Italy; furthermore, we provide data on the association between 25(OH)D deficiency and higher CCV risk factors.